THE NARRATIVE OF GENDER ON INSTAGRAM CAPTION - Rutmiarta Gultom; Dian Qamarina; Dery Rovino; Michael Jibrael Rorong (Asosiasi Ide Bahasa Kepri, 2020)
Instagram is one of the most famous social media for the number of millennials in Indonesia. There are around twenty-two million Indonesian users of Instagram according to Instagram Monthly Active Users data. It was dominated by millennial users. Instagram is likable because everyone feels free to share their creativity in a fun way. There are many Instagram users from several gender men or women and circles such as influencers, celebrities, educators, politicians, etc. Instagram was chosen for this research because Instagram gives Millenials opportunities to write freely, so this means caption Instagram will be a great place to get some information about the reliability of gender stereotypes in their writing. This research takes the focus of the study of gender language style on Instagram captions endorsement and decides to choose some influencer as a target of research. This research aims that there is a slight difference between men's captions and women's captions on Instagram, especially on how they deliver the endorsement product. This research use critical discourse analysis (CDA) and text as a critical objective (TACO) as a methodology to analyze Instagram captions. The result of this study will be the literature that fills the information gap how the existing theory or some statement about women and men's writing style reliable to the reality in the Instagram caption.